2017
DOI: 10.1093/jac/dkx347
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical testing of a broad-spectrum antimicrobial endotracheal tube coated with an innate immune synthetic mimic

Abstract: Thin films containing CSA-131 provide protection against microbial colonization of endotracheal tubes. This protection prevents fungal and bacterial biofilm formation on the tubes and reduces endotoxin associated with tubes. This coating is well suited for decreasing the adverse effects of intubation associated with infection and inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 34 publications
0
42
0
Order By: Relevance
“…Nagent, et al, [9] conducted a biofilm study using confocal microscopy and their images revealed that ceragenins efficiently penetrated established biofilms and led to cell death without significant alterations to the extracellular matrix. Additionally, a recent study demonstrated prolonged inhibition of biofilm formation on endotracheal tube surfaces when the tubes were coated with a CSA-131-containing hydrogel [30].…”
Section: Resultsmentioning
confidence: 99%
“…Nagent, et al, [9] conducted a biofilm study using confocal microscopy and their images revealed that ceragenins efficiently penetrated established biofilms and led to cell death without significant alterations to the extracellular matrix. Additionally, a recent study demonstrated prolonged inhibition of biofilm formation on endotracheal tube surfaces when the tubes were coated with a CSA-131-containing hydrogel [30].…”
Section: Resultsmentioning
confidence: 99%
“…34,35 A recent preclinical study reported reduced colonization in ETTs coated with a hydrogel film eluting ceragenin CSA-131, a non-peptide small molecule mimicking innate immune defense antimicrobial peptides. 36 Another approach to prevent biofilm growth without the use of coatings is to alter the PVC surface of the ETT's internal lumen. ETTs are modified creating grooves or roughness on their inner surface; the hypothesis is that altered PVC physical properties could lead to reduced microbial adhesion or could facilitate secretion movement.…”
Section: Treatment Of Ett Surfacementioning
confidence: 99%
“…Not only are spores an obvious concern in a number of applied settings, but there is continued interest in the development of new agents that are active against a variety of growing bacteria, especially in view of the rise of antibiotic‐resistant organisms that cause human disease. One class of antimicrobial agents developed recently is the membrane‐active ceragenins (Niemirowicz et al ; Pogoda et al ; Piktel et al ,; Hashemi et al ). Generally, the most active member of this family is ceragenin CSA‐13 (hereafter CSA‐13) (Fig.…”
Section: Introductionmentioning
confidence: 99%